2014
DOI: 10.5560/znb.2014-4147
|View full text |Cite
|
Sign up to set email alerts
|

Structures of Tetrasilylmethane Derivatives C(SiXMe2)4 (X=H, F, Cl, Br) in the Gas Phase and their Dynamic Structures in Solution

Abstract: The structures of the molecules C(SiXMe2)4 (X=H, F, Cl, Br) have been determined by gas electron diffraction (GED). Ab initio calculations revealed nine potential minima for each species, with significant ranges of energies. For the H, F, Cl, and Br derivatives nine, seven, two, and two conformers were modelled, respectively, as they were quantum-chemically predicted to be present in measurable quantities. Variable-temperature 1H and 29Si solution-phase NMR studies and, where applicable, 13C NMR, 1H/29Si NMR s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…By independently setting the two XMe 2 Si to all possible combinations of these angles, it can be seen that there are nine (=3 2 ) possible minimum-energy conformers for each of 1 – 3 . Experience of studying a similar set of species (XMe 2 Si) 4 C, where X = H, F, Cl, Br, has shown that the opposite sense of each angle (i.e., −80, +40, and +160°) should also be considered when looking to identify all possible conformers …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…By independently setting the two XMe 2 Si to all possible combinations of these angles, it can be seen that there are nine (=3 2 ) possible minimum-energy conformers for each of 1 – 3 . Experience of studying a similar set of species (XMe 2 Si) 4 C, where X = H, F, Cl, Br, has shown that the opposite sense of each angle (i.e., −80, +40, and +160°) should also be considered when looking to identify all possible conformers …”
Section: Methodsmentioning
confidence: 99%
“…Experience of studying a similar set of species (XMe 2 Si) 4 C, where X = H, F, Cl, Br, has shown that the opposite sense of each angle (i.e., −80, +40, and +160°) should also be considered when looking to identify all possible conformers. 40 All calculations used Gaussian 09 41 on either the University of Edinburgh's ECDF cluster 42 or the UK's National Service for Computational Chemistry Software clusters. 43 Geometry optimizations and frequency calculations were carried out to determine which ground-state conformers had the lowest energies.…”
Section: ■ Introductionmentioning
confidence: 99%